2010
DOI: 10.4236/health.2010.28130
|View full text |Cite
|
Sign up to set email alerts
|

Role of irrational beliefs in depression and anxiety: a review

Abstract: Irrational beliefs play a central role in cognitive theory and therapy; they have been shown to be related to a variety of disorders such as depression and anxiety. Irrational beliefs, which can be assessed via clinical interviewing techniques, are frequently assessed by self-report measures, both clinically and for research purposes. Much of the research demonstrating the effect of irrational beliefs has utilized such measures. The present article reviews the empirical work on irrational beliefs assessment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 68 publications
5
45
0
1
Order By: Relevance
“…First, a potential association between COMT Val 158 Met and irrational beliefs is in line with previous research that has associated this polymorphism to less cognitive flexibility (Bilder, Volavka, Lachman, & Grace, 2004), a hallmark of irrational beliefs (Dryden, 2003).…”
Section: Empirical Argumentssupporting
confidence: 53%
“…First, a potential association between COMT Val 158 Met and irrational beliefs is in line with previous research that has associated this polymorphism to less cognitive flexibility (Bilder, Volavka, Lachman, & Grace, 2004), a hallmark of irrational beliefs (Dryden, 2003).…”
Section: Empirical Argumentssupporting
confidence: 53%
“…Demandingness refers to inflexible requirements expressed in terms of ''musts,'' ''should,'' ''have to,'' and ''oughts'' (e.g., ''I should not have difficulties;' ' Bridges, 2010). In pain research it appears that demandingness, in the form of perfectionism, has a direct correlation with pain interference and negative affect (Hadjistavropoulos, Dash, Hadjistavropoulos, & Sullivan, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…However, LFT also implies a cognitive evaluation of certain circumstances as being unbearable (e.g., ''I can't function when I have difficulties;' ' Bridges, 2010). Although this irrational belief has not been a focus of study in chronic pain, McCracken and Eccleston (2003) have suggested that frustration, such as when attempts to control pain fail, can worsen the pain experience.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations